MANFAAT PENDEKATAN SISTEM DALAM PENYELESAIAN PERMOHONAN KEPAILITAN DI PENGADILAN NIAGA - Edi Krisharyanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
Law system plays a quite role in decision of the judge in a court, so the decision is expected to reflect a pure justice. It starts with the submission of the case, the process or the executive of the case and finally, decision from the judge. By the system approach, this decision is called the output. The feedback is a reaction of the decision that the bankrupt party able to institute to the Supreme Court.